A Comparative Analysis of Sports Betting Motivation Among University Students Based on Their Participation in Sports - Hüseyin Mete GÜNDOĞDU; Betül ALTINOK; Halil BİŞGİN (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2024)
This research aims to assess the prevalence of sports betting habits among university students and to evaluate the motivation levels of students engaged in sports betting based on their participation in sports activities. The study population comprises students from Kütahya Dumlupınar University and Bilecik Şeyh Edebali University. The SPSS 20.0 software was utilized for data analysis, and the data distribution was assessed. Percentage and frequency distributions were employed as a form of descriptive statistics in the data analysis. The "Independent Sample T-Test" was employed to assess the differences between the variables, with the significance level of the results evaluated at p<0.05. Our findings indicated that nearly two-thirds of university students engage in sports betting. Male university students exhibit a higher propensity to engage in sports betting compared to their female counterparts, and individuals who participate in sports are more inclined to bet on sports than those who do not partake in athletic activities. The students' family income level did not significantly influence sports betting rates; nevertheless, individuals who see sports betting as addictive are less like to engage in it, whereas those who believe that sports betting outcomes are manipulated are more likely to participate in betting activities. Analysis of sports betting motivation levels among university students reveals no significant difference in intrinsic motivation; however, extrinsic motivation and overall motivation levels show a significant difference favoring students who engage in sports. Our study's findings indicate that male university students engaged in sports represent the primary demographic for the sports betting industry, which places this group at significant risk for developing sports betting addiction.